Heather and homicide - MacRae, Molly (MacRae, Molly. Highland bookshop mystery series, 2020)
"True crime writer Heather Kilbride arrives in the seacoast town of Inversgail, Scotland, to research a recent murder for her new book. But if that's true, why does she seem more interested in William Clark, a shadowy lawyer with no connection to the murder? Her nosy questions arouse the suspicions of Constable Hobbs, the members of a local writers' group, and Janet Marsh and her crew of amateur sleuths at Yon Bonnie Books. Heather's unconventional research methods prove deadly when Janet discovers her lifeless body. Except the body turns out to be a dummy dressed-up to look like Heather. Meanwhile, Heather is sitting at a safe distance observing Janet's reactions. Then Heather is found dead--again--sprawled at the base of an ancient standing stone; and this time it's for real. Clutched in her hand is a valuable miniature book last seen at Yon Bonnie Books, and now the police want to know how Heather, the miniature book, and Janet are all connected. But Janet and her group of sleuths have two questions of their own: Who else is interested in knowing that connection-and is that person a cold-blooded killer?"--Provided by publisher.